The Measurement of Intelligence 1973
DOI: 10.1007/978-94-011-6129-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Personality and the Measurement of Intelligence

Abstract: SUMMARY.A re-analysis is presented of some data purporting to show that stable children differ from labile ones with respect to the structure of their intellectual abilities. The hypothesis is supported, and additional data are presented tending to show that theories of linear independence between cognitive and non-cognitive areas may have to be supplemented by theories stressing non-linear dependence.It is usually maintained that intelligence is statistically independent of temperamental factors such as neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 9 publications
0
24
1
Order By: Relevance
“…For example, Austin et al (1997) found a significant positive quadratic relationship between neuroticism and intelligence, contradicting the past arguments by showing that higher test performance generally occurs for those with either high or low levels of neuroticism. Similarly, the neuroticism-differentiation hypothesis suggests that cognitive abilities are less differentiated at increased levels of neuroticism, and conversely more differentiated at decreased levels of neuroticism (Eysenck & White, 1964; see also Austin et al, 1997). In other words, g should account for more of the total observed variance in a battery of ability tests at high levels of neuroticism than it should at low levels.…”
Section: Personalitymentioning
confidence: 94%
“…For example, Austin et al (1997) found a significant positive quadratic relationship between neuroticism and intelligence, contradicting the past arguments by showing that higher test performance generally occurs for those with either high or low levels of neuroticism. Similarly, the neuroticism-differentiation hypothesis suggests that cognitive abilities are less differentiated at increased levels of neuroticism, and conversely more differentiated at decreased levels of neuroticism (Eysenck & White, 1964; see also Austin et al, 1997). In other words, g should account for more of the total observed variance in a battery of ability tests at high levels of neuroticism than it should at low levels.…”
Section: Personalitymentioning
confidence: 94%
“…Cattell (1957), for example, was convinced that many 'pure' personality factors have some substantial intellectual ability component and that the general ability influences some of these genuinely personality manifestations such as scope of interests or achievement motivation. Empirical studies, however, have typically found only a modest correlation between measures of personality and intelligence (Eysenck, 1994;Goff & Ackerman, 1992;Zeidner, 1995; for a metareview see Ackerman & Heggestad, 1997). Openness to Experience as measured by the Revised NEO Personality Inventory seems to be consistently related to psychometrically measured intelligence and other cognitive abilities (McCrae & Costa, 1997;Moutafi, Furnham, & Crump, 2003).…”
Section: Personality and Intellectual Abilitiesmentioning
confidence: 99%
“…The notion of a curvilinear relationship between neuroticism and cognitive performance has been discussed previously on a conceptual level (Eysenck, & White, 1964;Brand et al, 1994). The reported study contributes with empirical evidence to this discussion.…”
Section: -------------------------------mentioning
confidence: 99%
“…If trait neuroticism is identified with arousal or autonomic drive (Eysenck & White, 1964;Lynn & Gordon, 1961), and assuming that tasks in cognitive ability tests like the Raven"s Progressive Matrices are of moderate difficulty to most individuals, it follows that both high and low levels of trait neuroticism are less effective than 4 moderate levels of trait neuroticism in terms of performance on such tasks. Note however, that the Yerkes-Dodson law refers to within-person differences in the subjective experience of arousal when dealing with a cognitive task, which is arguably different from between-person structural differences in neuroticism as typically studied.…”
Section: The Non-linear Neuroticism-performance Effectmentioning
confidence: 99%
See 1 more Smart Citation